The Philosophy of Education in Viet Nam Nowadays - Hieu, Tran Minh (RA Journal of Applied Research, 2021)
The philosophy of education is always an essential issue of every education system. Over the past 70 years, depending on the stage of educational development, Vietnam's educational philosophy has existed and changed many times. So what is the educational philosophy in Vietnam nowadays? There are too many views on this. In this article, we present our views on this extremely important issue. The research results are based on the methodology of systematization, the methods of analysis – synthesis and comparison. We also use some conclusions of Vietnamese researchers as references. Indeed, Vietnam's educational philosophy can be divided into two periods: before 1945 and after 1945. Before 1945, Vietnam's educational philosophy was largely influenced by Confucianism, so ideal model was "quan tu" (true gentleman) people. After 1945, the country was independent, the philosophy of education was aimed at training the new socialist people. This change, on one side, meets the requirement to maintain social stability, but the other side is not paying attention to individual people and their creation. This leads to the crises of the whole education system, especially in the context of globalization and internationalization. The new context is setting new requirements for the educational philosophy of Vietnam. From a philosophical point of view, with reconsidering the human nature in general, we suppose that the new educational philosophy of Vietnam nowadays must be training freedom, creativity and bravery people, based on a human. In this article, we will raise different views of many scholars about it and present our points of views on this extremely important issue. In this article, we will denote different conceptions of many scholars about it and take our view on this extremely important issue. Hereafter indicating the educational achievements of Vietnam in the past, we introduce the system of perceptions about the human in Vietnamese society today and regarding this as the basis for building the philosophy of education and showing the basic ideas of the educational philosophy, which exists in Vietnam nowadays. Finally, we state our views on this issue. It is a combination of ideas that are difficult to say in a sentence.